Did you hear your action? An ecological approach to the senses of ownership and agency. (February 2023) - Re, Anna; Perconti, Pietro; Malvica, Sonia; Castano, Emanuele
The Sense of Ownership (SoO) and the Sense of Agency (SoA) are two key components of bodily self-consciousness. In this experiment, we investigated how they are affected by variations in the ecological validity of the moving Rubber Hand Illusion (mRHI) paradigm, which typically include three movement conditions: active congruent, passive congruent, and active incongruent. These conditions were either in a session in which no auditory feedback associated with finger-tapping was eliminated, or in a session in which such a feedback occurred. Since the presence of the auditory feedback more closely corresponds to what individuals experience in daily life when they tap their finger on a surface, sessions with feedback are more ecologically valid, and should thus result in a more marked SoO. Results indicated that in the active movement condition in which the illusion is typically found (congruent), the effect was enhanced when the feedback was present. This advantage emerged on both on objective and subjective measures of SoO. The SoA, on the other hand, is not affected by the auditory feedback.